Highly recommended : - Stott, Trish (Oxford University Press, 2004)
This is a popu;ar elementary-level course for younger adult learners on hotel and catering courses in school and colleges or people training for career in the hospitality sector. It provides the English needed for dealing with customers and colleagues in a variety of hotel and restaurant situations such as taking bookings, checking guests in and out; dealing with enquiries and complaints, explaining dishes; taking payments